On Corruption and Capital Accumulation - Juan-Ramon, V. (IMF Working Papers; Working Paper ;, 1994)
Reforming economies have typically placed little attention on the impact of illegal activities on the success of reform/stabilization packages and optimal policy design. This paper aims at developing a framework in which to assess an economy's response to alternative stabilization/reform packages as a function of the scope of corruption activities. The framework developed herein is a basic one in which only the most fundamental questions (such as the effects of anti-corruption government policies on output and welfare) are examined. The more interesting questions of the optimal design of stabilization and economic reform policies remain to be addressed in future extensions of the model. The framework also accommodates political-economy analysis, and is able to explain why, even when able to eliminate corruption activity altogether, governments may choose not to do so. Our framework differentiates between developing and developed economies according to the income share accruing to capital, as is common in the literature. In equilibrium, the effect of anti-corruption penalties on the economy's capital stock is greater in developing countries; in particular, we find that the elasticity of the steady state average per capita stock of capital with respect to increases in anti-corruption penalties is increasing in the income share accruing to capital. The model also shows that reductions in public good output, as a fraction of the economy's total expenditure, lead to larger welfare decreases when in the presence of corruption.